Urethane acrylate and silicon acrylate containing novel epoxy acrylate systems for sla 3d printers - AKIN, EMRE; ÇAKIR, MUSTAFA (My University, 2022)
As well known, epoxy acrylate resins have been widely used in 3D SLA printer applications. Epoxy acrylate systems have generally consisted of bisphenol-A glycerolate diacrylate (epoxy acrylate resin) and 1,6-Hexanediol diacrylate (HDDA, reactive diluent resin) in various weight percents. The purpose of this study is to develop novel epoxy acrylate systems without HDDA and investigate their properties. For this reason, two different reactive resins were used instead of HDDA in epoxy acrylate systems with various weight percents. One of these resins was urethane acrylate resin that was synthesized in our laboratory. Urethane acrylate resin was synthesized using monomeric aliphatic diisocyanate (commercial name; Desmodur H) and 2-Hydroxymethyl methacrylate (HEMA). The other reactive resin was mixture of silicone acrylate and photoinitiator (commercial name; TEGO RC 1002). These resins were added into epoxy acrylate resin in various weight percent such as 20%, 40%, 60% and 80%. Tensile, izod impact, shore-D hardness, taber abrasive, density and DSC tests were applied to these produced samples. Considering of the results, urethane acrylate containing epoxy acrylate system exhibited much more improved results compared to pure epoxy acrylate system and silicon acrylate containing epoxy acrylate systems. It also exhibited more enhanced properties than epoxy acrylate systems with HDDA. It exhibited substantial increases in terms of tensile strength, modulus and izod impact resistance. Moreover, they presented more enhanced abrasive resistance. Shore-D hardness values and densities showed almost no change. This synthesized urethane acrylate reactive resin can be used in applications that required higher mechanical and abrasive properties for epoxy acrylate systems of 3D SLA printers.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)